The historical study of women: England 1500 - 1700 - Capern, Amanda L. ca. 20./21. Jh. (Palgrave, 2008)
"In this reference guide, Amanda L. Capern provides a detailed survey of the history and historiography of early-modern women in England. Covering a wide variety of topics, she offers new constructions of several aspects of women's history such as ideas about women, the intersection between law and private life, women and religion, women's secular and political writing, and women and the English Civil War. Capern also demonstrates the ways in which women were seen as having a dual nature - whores and wives, scolds and saints - and argues that they themselves were responsible for rescuing their sex from a negative construction of femininity." "The Historical Study of Women examines the intellectual and social place of women in early-modern society and offers a new interpretation of the processes of gender change between 1500 and 1700. Clear and comprehensive, this survey is an invaluable resource for all those interested in Early Modern or Women's History."--BOOK JACKET